Barriers and facilitators influencing the choice of a vegetarian menu in a university cafeteria - Valeria A. Bertoni Maluf; Sidonie Fabbi; Carolina Cerqueira Azevedo; Isabelle Carrard (Journal of Nutritional Science)
This cross-sectional study examined the barriers and facilitators that influence vegetarian menu choices in a university cafeteria in Geneva, Switzerland. As a first step, an online survey developed by the authors based on the Capability, Opportunity, and Motivation Behaviour (COM-B) model was e-mailed to all university students and staff. In the second step, focus groups (FG) were held to complete the survey responses and identify what needed to be changed to promote the choice of the vegetarian menu in the cafeteria. Data from 304 participants collected through the survey was analysed. The main mentioned barriers were lack of vegetarian options, tastelessness and insufficient satiation. The facilitators that emerged from the survey were the price of the vegetarian menu for students and health and environmental benefits. Thirteen people participated in four FG sessions, which were analysed using thematic analysis. Five themes were identified: spontaneous menu selection, predefined menu selection, influence of opportunity on menu selection, influence of environmental sensitivity on menu selection, and threat to identity in menu selection. The choice of a vegetarian menu in a university cafeteria was mainly influenced by the attractiveness and taste of the plate. Future strategies to reduce food-related greenhouse gas emissions should (a) ensure the quality and attractiveness of the vegetarian menu, especially to appeal to the more resistant, such as men and omnivores, and (b) inform consumers about the guarantee of balanced nutrient intake of the vegetarian menu offered in the cafeteria, and about health and environmental benefits.